Science education practices for deaf and hard-of-hearing students in Indonesia - Nandya Atika, Iva; Putranta, Himawan; Kawai, Norimune; Hayashida, Masashi; Shinkai, Akira (Specijalna edukacija i rehabilitacija, 2023)
Introduction. Traditionally, the curriculum for deaf learners mainly involved language acquisition at the expense of other academic subjects. Currently, their subjects also include other disciplines, like science, to enrich students' knowledge related to human life. Objective. This qualitative study describes current school science learning practices and identifies the challenges in improving science education for deaf and hard-of-hearing (DHH) students. Methods. We selected four principals and six classroom science teachers from five DHH schools as participants, using purposive sampling in the five schools in three regencies of Regional V Banyumas, Central Java, Indonesia. Data were gathered through interviews, field observations, and artifacts. Results. Science education practices for DHH students—classroom practices, school support, and teacher collaboration—guided the data collection and analysis. The teachers use various teaching strategies and rely on visual and hands-on activities for DHH students. The schools provide sign language interpreters and speech-development programs as support for teachers and DHH students. All teachers need professional development and collaboration opportunities to develop their expertise to teach DHH students. Intrinsic and extrinsic factors were found to create barriers for DHH students in science education. DHH students' literacy, sign language, cognition, and motivation were found as intrinsic factors. The policy implementation, instructional strategies, resources, and teacher qualifications were found as extrinsic factors. Conclusion. The teachers need support from the government to include them in relevant training programs and prepare teachers with special or inclusive education knowledge by adding courses in university-level education for all prospective teachers. The results are insightful for DHH students, science educators, and policymakers.
Keywords: Deaf and Hard-of-Hearing students; education practices; inclusive education; science education